Benzo[1, 2‐b:4, 5‐b′]Dithiophene–6, 7‐Difluoroquinoxaline Small Molecule Donors with >8% BHJ Solar Cell Efficiency. Issue 20 (14th July 2017) - Liang, Ru‐Ze; Wang, Kai; Wolf, Jannic; Babics, Maxime; Wucher, Philipp; Thehaiban, Mohammad K. Al; Beaujuge, Pierre M.
Abstract: Solution‐processable small molecule (SM) donors are promising alternatives to their polymer counterparts in bulk‐heterojunction (BHJ) solar cells. While SM donors with favorable spectral absorption, self‐assembly patterns, optimum thin‐film morphologies, and high carrier mobilities in optimized donor–acceptor blends are required to further BHJ device efficiencies, material structure governs each one of those attributes. As a result, the rational design of SM donors with gradually improved BHJ solar cell efficiencies must concurrently address: (i) bandgap tuning and optimization of spectral absorption (inherent to the SM main chain) and (ii) pendant‐group substitution promoting structural order and mediating morphological effects. In this paper, the rational pendant‐group substitution in benzo[1, 2‐ b :4, 5‐ b′ ]dithiophene–6, 7‐difluoroquinoxaline SMs is shown to be an effective approach to narrowing the optical gap ( E opt ) of the SM donors (SM1 andSM2 ), without altering their propensity to order and form favorable thin‐film BHJ morphologies with PC71 BM. Systematic device examinations show that power conversion efficiencies >8% and open‐circuit voltages ( V OC ) nearing 1 V can be achieved with the narrow‐gap SM donor analog (SM2, E opt = 1.6 eV) and that charge transport in optimized BHJ solar cells proceeds with minimal, nearly trap‐free recombination. Detailed device simulations, light intensity dependence, and transient photocurrent analyses emphasize how carrier recombination impacts BHJ device performance upon optimization of active layer thickness and morphology. Abstract : Rational pendant‐group substitutions in benzo[1, 2‐ b :4, 5‐ b′ ]dithiophene‐6, 7‐difluoroquin‐oxaline small molecule donor analogs yield power conversion efficiencies >8% and high open‐circuit voltages nearing 1 V in bulk heterojunction (BHJ) solar cells with the fullerene acceptor PC71 BM. Charge transport in optimized BHJ solar cells proceeds with minimal, nearly trap‐free recombination.